Genetic Features of Clinical Isolates of Streptococcus dysgalactiae subsp. equisimilis Possessing Lancefield's Group A Antigen - Tanaka, Daisuke (American Society for Microbiology (ASM), 2008)
Thirteen Streptococcus dysgalactiae subsp. equisimilis isolates possessing Lancefield's group A antigen recovered from people in Japan during 2000 to 2004 were genotyped. The results indicate that a conserved clone has persisted and spread within Japan, and two different emm types were observed within members of this clone.